Assessing livelihood dependency on forestry products during COVID-19 period - Chiotha, Festus (Jurnal Bisnis Kehutanan dan Lingkungan, 2024)
Background: The importance of forest in improving human welfare is recognized worldwide. Both natural and artificial forests provide basic needs such as fuel wood, timber, industrial wood and non-timber products. They also provide employment, income and foreign exchange hence contributing to social and economic development. Equally important are the environmental benefits of forest. But as covid 19 came people lost their job, their movement was restricted as a result an increase dependency on forest products for survival increases in developing countries. Therefore, the main aim of the study was to unearth impacts of COVID-19 has on the forest products of people living around zomba plateau forest reserve. The general objective of the study is to assess livelihood dependency on forest product during COVID-19 period. Method: Specifically, the study will identify and assess which forest products were frequently accessed during COVID-19 and analyze the contribution of forest products on household income during the pandemic period. Both qualitative and quantitative methodologies were used to collect data. The target population for the study consisted of residents of Mtendere village. The sample size was 59. Data were collected using self- administered questionnaire and interviews. Qualitative and quantitative data was analyzed using statistical package for social sciences (SPSS) and excel package respectively. Result: The results of the study indicate that there was an increase dependency of forest products during COVID-19 period and such that the contribution the contribution of forest products to household income dwindles during this period. Conclusion: The study further recommends to build the resilience of forest- dependent communities to future shocks and crises. This can be achieved through the implementation of social safety nets, or savings and credit programs. Novelty/Originality of this study: This study presents the first comprehensive analysis of the impact of COVID-19 on community dependence on forest products and finds changes in forest resource use patterns during the pandemic. It provides new insights into the resilience of forest-dependent communities in the face of global crises. It offers practical recommendations for building community resilience through social safety nets and credit savings programs.